0698 Genetic susceptibility to elevated C-reactive protein and risk of obstructive sleep apnea in US men and women. (25th May 2022) - Huang, Tianyi; Goodman, Matthew; Wang, Heming; Sofer, Tamar; Tworoger, Shelley; Stampfer, Meir; Saxena, Richa; Redline, Susan
Abstract: Introduction: Obstructive sleep apnea (OSA) may trigger inflammation. However, growing evidence suggests a role for inflammation in predisposing OSA through increased upper airway size/collapsibility and altered ventilatory control. Inflammation also promotes sleep disturbance and excessive daytime sleepiness (EDS). Genetic analysis may provide further insights into the causal relationship between chronic inflammation and OSA incidence. Methods: In 33, 171 participants of European ancestry from the Nurses' Health Study (NHS), NHS2 and the Health Professionals Follow-up Study, we quantified genetic predisposition to inflammation using a weighted polygenic risk score (PRS) based on 51 loci identified for C-reactive protein (CRP) in a recent genome-wide association meta-analysis. OSA was determined using self-reported diagnoses, which were demonstrated to reliably indicate moderate-to-severe OSA in these cohorts. EDS was defined based on self-reports of disrupted daily activities due to sleepiness ≥4 days/week. Multivariable logistic regression was used to estimate the odds ratio (OR) for OSA risk according to the number of risk alleles, adjusted for age, sex, BMI, genotyping platforms and 10 genetic principal components. Mendelian randomization using individual-level participant data was performed to evaluate the association between genetically determined CRP levels and OSA risk. Results: A total of 3, 163 participants (9.5%) had clinically diagnosed OSA (575 with EDS). While the CRP PRS (explained 5.0% variance in circulating levels) was not associated with OSA risk overall (OR per increment of 5 risk alleles: 1.00; 95% CI: 0.96, 1.04; p=0.96), a significant positive association was observed for OSA with concurrent EDS (Comparable OR: 1.13; 95% CI: 1.04, 1.23; p=0.003). In contrast, among participants without clinically diagnosed OSA, there was no association between the PRS and EDS (Comparable OR for EDS: 1.02; 95% CI: 0.98, 1.06; p=0.28). In Mendelian randomization, each doubling of genetically elevated CRP was associated with 44% higher odds of OSA with EDS (95% CI: 1.13, 1.82). Conclusion: Chronic inflammation (characterized by elevated CRP levels) may be casually associated with risk of developing symptomatic OSA with EDS, but not OSA or EDS alone. To confirm our findings, future investigations are needed to evaluate the genetic associations with objective measures of OSA severity across diverse populations and elucidate mechanisms driven by specific inflammatory mediators. Support (If Any): NIH grants UM1CA186107, U01CA176726, U01CA167552, K01HL143034, R35HL135818